2013
DOI: 10.1080/10962247.2013.851044
|View full text |Cite
|
Sign up to set email alerts
|

Changes in weather and climate extremes: State of knowledge relevant to air and water quality in the United States

Abstract: Air and water quality are impacted by extreme weather and climate events on time scales ranging from minutes to many months. This review paper discusses the state of knowledge of how and why extreme events are changing and are projected to change in the future. These events include heat waves, cold waves, floods, droughts, hurricanes, strong extratropical cyclones such as nor'easters, heavy rain, and major snowfalls. Some of these events, such as heat waves, are projected to increase, while others, with cold w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 102 publications
(102 reference statements)
0
19
0
Order By: Relevance
“…There have not yet been any detected global trends in TC rainfall rates. 188 Chang et al 52 examined a multidecadal trend in rainfall from TCs affecting Taiwan. They found that the observed increases arose from relatively weaker typhoons and could largely be attributed to an increase in slow-moving systems.…”
Section: Tc Rainfall and Other Impactsmentioning
confidence: 99%
“…There have not yet been any detected global trends in TC rainfall rates. 188 Chang et al 52 examined a multidecadal trend in rainfall from TCs affecting Taiwan. They found that the observed increases arose from relatively weaker typhoons and could largely be attributed to an increase in slow-moving systems.…”
Section: Tc Rainfall and Other Impactsmentioning
confidence: 99%
“…Winter conditions are cooler, with occasional freezing and isolated snow or ice storms inland, but generally milder conditions along the northern coast of the Gulf of Mexico. The region also is known for its extreme weather conditions where drought occurs, tornadoes develop in large convective systems in summer and early fall, and tropical storms from the Atlantic Ocean and the Gulf of Mexico penetrate inland on occasion (e.g., Peterson et al, 2014). Extended summer periods of light winds and air mass stagnation are prevalent, leading to accumulation of pollution (e.g., McNider et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…2007). By markedly altering chemical (eg pH) and physical (eg temperature) parameters of aquatic ecosystems (Peterson et al . 2014), extreme events may also have far‐reaching effects.…”
mentioning
confidence: 99%